APPLICATION OF DEDUCTIVE INDUCTIVE LEARNING APPROACH IN IMPROVING WRITING SKILLS TEXT ANEKDOT - Saanan, Saanan; Sobari, Teti (JLER (Journal of Language Education Research), 2018)
Learning should be able to connect knowledge or materials to be learned with a sense that already owned a person so that understanding can be developed. In other words, learning must be changed from centered to teacher-centered to student-centered learning. An inductive-deductive approach is a learning approach that can enable students to build knowledge. on the material Writing anecdotal text. The purpose of this research is to know the effectiveness of Learning with an inductive-deductive approach. The population of this study is all students of class X. The research design used is posttest only control design. The sampling technique used is cluster random sampling, Hypothesis testing is done using t test to posttest value. From the results of the hypothesis test obtained pretest value of 60.40 and posttest grade experimental class has reached mastery learning with a portion of 73.05. In testing affective and psychomotor aspects, the average value of experimental class learning outcomes is better than control class. Based on the result of the research, it is concluded that the learning with the inductive-deductive approach is effective on the result of learning Indonesian on the material of writing anecdotal text.